Sources and Uses of Water in the Oil Industry - Deep Groundwater Aquifers (Achebyat and Hasawnah), SW Murzuq Basin, Libya - Sadeg M Ghnia (The Libyan Journal of Science, 2024)
Deep water sources are important in providing the amount of water required to be injected into the oil reservoirs to maintain reservoir pressures and to avoid a decrease in pressure below bubble point, which directly affect oil production and reserves. This objective of this study was to identify the deep aquifers water sources potential and quality of the Achebyat and Hasawnah formations within NC200 block, to be injected into the Erawin field Mamuniyat reservoir. The study provides a geological description of Achebyat and the Hasawnah formations, estimate the water volume, investigate the water productivity, determine water salinity, and propose optimum water source wells location. Seismic data, core and wireline logs information including image logs, well test results and outcrop information were used for this study. The Achebyat aquifer has a mean porosity of 12.4%, while Hasawnah has lower porosity than Achebyat with a mean value of 8.8%. The bulk rock volume is about 13.9 trillion cubic-feet, and the estimated water volume is 992 billion barrels. The required makeup water for water injection would be 16,5000 bbl/d, around 6 million barrels per year. E6-NC200 Achebyat-Hasawnah production test rate was 1,360 bbl/d. In this test, the determined PI was 2.0 bbl/d/psi. Water salinity was estimated during the well E6-NC200 production test to be 2000 ppm. The Achebyat and Hasawnah deep groundwater aquifers in the study area can be used, in addition to the oil industry, as a source for drinking and agricultural water after simple treatment.